Efektivitas Penerapan Program Layanan Informasi Non-MITA di KPUBC Tanjung Priok - Pribadi, Jiwa; Shiddiq, Muhammad Ilham; Harjo, Dwikora (JAMBIS : Jurnal Administrasi Bisnis, 2025)
The need for fast, transparent, and efficient information services has encouraged the Tanjung Priok Type-A Customs and Excise Main Service Office to implement the Non-MITA Client Information Service Registration Application. This study aims to analyze the effectiveness of the implementation of the program in increasing access to customs, excise and taxation information, identifying the obstacles faced, and the solutions implemented. The method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, documentation, and triangulation. The analysis uses Amitai Etzioni's theory of organizational effectiveness, which includes four dimensions: adaptation, integration, motivation, and production. The research results show that this application is quite effective in improving the quality of information services, although there are still obstacles such as limited quotas, lack of human resources, and user absence from service schedules. The solutions implemented include improved communication, better queue management, and regular service evaluation. Overall, the program implementation is considered to have met most of the effectiveness indicators according to Etzioni, but still requires improvement to be more adaptive to the dynamics of user needs.